Re-examining Social Verses through Justice and Inequality: A Critical Hermeneutical Approach to Qur’anic Exegesis - Abdul Karim; Moh. Muhtador (QOF, 2025)
The problem of social inequality reflects inequality in power relations, distribution of resources, and ideological legitimacy, which are often wrapped in religious narratives. In fact, the Qur'an contains fundamental values such as justice, solidarity, equality, and defense of the oppressed (mustaḍ‘afīn). This article aims to re-examine in depth the approach of social interpretation of the Qur'an in responding to issues of socioeconomic inequality and to reveal the role of the Qur'an in defending social inequality. The research includes a literature study with a critical hermeneutic approach in reading social verses in interpretations that are in accordance with the characteristics of interpretation. The primary source refers to verses of the Qur'an relating to the principle of economic justice, and some other related literature as secondary sources. This article argues that the social verses of the Qur’an are grounded in the principles of justice (al-‘adl), compassion (raḥmah), and egalitarianism (musāwah). These spirits are in line with social interpretation based on a critical hermeneutical framework that connects the text, context, and social reality. The findings reveal that social exegesis not only interprets the text normatively but also presents it as a tool for social criticism against entrenched structures of injustice. This exegesis promotes the formation of transformative ethics that favour marginalised groups. This research opens up a space for dialogue between religious texts and the practice of social justice in the context of contemporary Muslim society, and expands the horizon of exegesis as a tool for social change.